Schinkel’s influences on Mies’s brick architecture. From the Bauakademie to the Perlstein Hall - Santatecla-Fayos, José; Lizondo-Sevilla, Laura; Merino-Salazar, Rodrigo (Estoa. Journal of the Faculty of Architecture and Urbanism, 2024)
Although Mies van der Rohe’s architecture is often associated with steel and glass, he had a fondness for brick and used it in both Europe and the Americas. For this reason, and because it has received little attention in the academic literature, this article investigates its use in Mies’s work from the perspective of Karl Friedrich Schinkel, an architect known for his innovative use of the material.110 years elapsed between the Bauakademie and Perlstein Hall, a period in which the study variables are clearly visible: Mies’s most important projects are reviewed and compared with Schinkel’s buildings, all of which were designed in brick. This research provides clues how Schinkel influenced Mies’s architecture, demonstrates that both architects used a classic material in a modern, honest way, and which Mies was able to push to its furthest limits by individualising the load-bearing and enclosing functions of the wall in his projects.